KEKHASAN CERITA PENDEK JAWA MODERN (CERKAK) ABAD 21: KAJIAN IDEALISME PENGARANG DAN KARAKTERISTIK KARYANYA - Suwarni, Suwarni; Sulistiani, Sri (Jurnal Pena Indonesia, 2016)
Short story of Java language is one genre in modern Javanese literature. Short story (cerpen) in a modern Javanese literature termed insufficient story (cerkak). The focus of this study of short stories is the Java language short stories contained in the Java-language magazines, such as magazines and periodicals Panyebar Jaya Baya spirit. Both of these magazines is a barometer of Javanese literature in East Java. This paper mengulik about how the position of women in the Java language short stories in 2002 ?; the extent of short stories in 2002 Java language reflects the role and status of women as found in the real world ?; and can speak Javanese short story of 2002 is used as one of the media in an effort to improve the quality of women? This paper argues that there are substantive role and the role of Achievement in the short story is the role of women outside the home, for example, the role of women in associations, organizations, and the role of world prestatif.Â